The Effects of Mouthwashes on the Color Stability of Resin-Based Restorative Materials - Ertürk-Avunduk, Ayşe Tuğba; Aksu, Seçkin; Delikan, Ebru (Odovtos - International Journal of Dental Sciences, 2020)
Objective: This study investigated the effects of three types of mouthwash on the color stability of three resin-based restorative materials (nanohybrid resin composite, sonic-activated bulk-fill material, and compomer). Materials and Methods: To this end, 120 cylindrical disc specimens were prepared and polished, after which they were incubated in distilled water for 24 hours for post-polymerization. The baseline color values of each specimen were measured with a spectrophotometer, then the specimens were randomly divided into four groups. Following immersion in the mouthwashes for 24 hours, the specimens were rinsed with distilled water and dried before the color measurement was repeated. The values of color change (∆E₀₀) were subsequently calculated. A two-way analysis of variance and Duncan’s post hoc multiple comparison tests were conducted to determine statistically significant differences among the restorative materials. Results: All samples showed discoloration after immersion, albeit some instances of discoloration were imperceptible. In this respect, a statistically significant difference was found among the restorative materials and mouthwashes (p<0.05). Imperceptible ∆E₀₀ values were derived on the nanohybrid resin composite and compomer, but perceptible and acceptable ∆E₀₀ values were detected on the sonic-activated bulk-fill materials (p<0.05). The clinically unacceptable discoloration was observed on the sonic-activated bulk-fill composite immersed in Listerine®. Conclusions: Clinicians should make recommendations based on the potential staining capacity of mouthwashes prescribed for daily use in restorative materials. In this way, the need for renewal of restorations due to discoloration could be avoided.